Cytohormonal patterns in mature and pre-term babies. Issue 1 (January 1979) - Cummins, M; Gordon, H; Hudson, E; Wachtel, E
Abstract : Comparison of cytohormonal patterns in full-term and pre-term babies of both sexes showed significant differences. At birth, irrespective of gestational age, both groups had high oestrogen levels, reflecting the maternal hormonal environment, but whereas the mature neonates were capable of metabolising and excreting the excess hormone within the first week of life, the pre-term infants took much longer to do so. It is thought that immaturity or impairment of liver function is at least partially responsible for this finding.